Total synthesis of (+/-)-quinagolide: a potent D-2 receptor agonist for the treatment of hyperprolactinemia - Chavan, Subhash P.; Kadam, Appasaheb L.; Kawale, Sanket A. (ACS Omega, 2019)
A potent dopamine (D-2) receptor agonist (+/-)-quinagolide, which is used for the treatment of hyperprolactinemia, was synthesized using the ring closing metathesis (RCM) approach from meta-hydroxybenzaldehyde as the starting material. The key features of this synthesis are pyrolytic elimination, late-stage expedient synthesis of functionalized trans-fused tetrahydropyridine-3-carboxylates from olefin 6, via conjugate addition-elimination upon acetate 11, followed by RCM and phenyliodine bis(trifluoroacetate) (PIFA)-mediated Hofmann rearrangement of piperidine-3-carboxamide, which enables the synthesis of 3-aminopiperidine skeleton of quinagolide. For the total synthesis of natural products such as ergot alkaloids, late-stage synthesis of functionalized trans-fused tetrahydropyridine-3-carboxylates using RCM and PIFA-mediated Hofmann rearrangement of piperidine-3-carboxamide, which allows quick access to the synthetically challenging 3-aminopiperidine skeleton, are the main achievements of the present work.